First experimental measurements of a new fast ion driven micro-burst instability in a field-reversed configuration plasma. (22nd October 2018) - Deng, B.H.; Douglass, J.D.; Roche, T.; Belova, E.V.; Beall, M.; Binderbauer, M.W.; Clary, R.; Dettrick, S.A.; Gota, H.; Granstedt, E.; Korepanov, S.; Magee, R.M.; et al.
Abstract: In modern field-reversed configuration (FRC) experiments (Binderbauer et al 2015 Phys. Plasmas 22 056110) at TAE Technologies, classical FRC instabilities are suppressed by advanced neutral beam injection and edge biasing methods, leading to high plasma confinement and fast ion pressure built-up which is comparable to the bulk plasma pressure. In some of these high performance FRC plasmas, a new macroscopically non-destructive fast ion driven micro-burst instability is observed as periodic small amplitude bursts with frequency down chirping in the diamagnetic drift frequency range, repeating about every 0.1 to 0.5 ms. The occurrence of these micro-bursts and burst-free operation can be controlled by changing the injected neutral beam energy. Major observed characteristics of this new instability are presented. Possible explanation of the phenomenon is suggested.